ChemInform Abstract: Enantioselective Homocrotylboration of Aliphatic Aldehydes. Issue 25 (3rd June 2013) - Lin, Hongkun; Pei, Wenbo; Wang, Hao; Houk, Kendall N.; Krauss, Isaac J.
Abstract The method to prepare optically pure syn‐homocrotylation products is developed.